ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI JUMLAH KUNJUNGAN WISATAWAN DI KABUPATEN PESISIR SELATAN JAWA TIMUR - Djauharotun Nafisah; Arief Bachtiar (Universitas Nias Raya, 2025)
This study aims to analyze the factors that influence the number of tourist visits in the Pesisir Regency of East Java in 2014-2023. The Pesisir Regency of East Java is a regency with a long coastline bordering the Indian Ocean so it has stunning coastal tourism, and this results in differences in the number of tourist visits in each region according to the views presented in each region. The independent variables are the Number of Hotels, Number of Tourist Attractions, Labor, Minimum Wages, Cultural Attractions, and Relaxation Places and the number of tourist visits as the dependent variable. The research data uses a quantitative approach with panel data regression of 7 Coastal Regencies of East Java with sources from the Central Statistics Agency (BPS) and the Tourism Office, using the Fixed Effect Model. The results show that not all variables have a significant effect on the number of tourist visits, the variables of labor, minimum wages, cultural attractions, and relaxation places have a significant effect on the number of tourist visits while the number of hotels and tourist attractions has no significant effect on the number of tourist visits. This explains that the importance of cultural and relaxation aspects supports the sustainability of the tourism sector in the coastal areas of East Java.